Answer: x=-2 y=2
Step-by-step explanation:
I decided that isolating the y value of the second equation is the best way to start solving.
I divide 3 from both sides to get y= (4-x)/3. With this, I can substitute into the first equation. 4x+3(4-x)/3)=-2.
The multiplying the 3 by the denominator three cancels each other out to make:
4x+4-x=-2.
We subtract 4 on both sides and then subtract x from 4x.
We end up with 3x=-6. Then, we divide both sides by 3.
x=-2.
Now we substitute this into the second equation to solve.
3y=4-(-2)
This becomes 3y=4+2 which is 3y=6
We divide both sides by 3 to get y=2
We end up with x=-2 and y=2.
I hope you learned something :)
Answer:
10
-------------
3x^2
Step-by-step explanation:
First lets simplify what is inside the square root
300x8
---------------
27x12
3 * 100 x^8
------------------
3 *9 x^12
The 3's cancel and we know a^b/ a^c = a^(b-c)
100/9 x^ (8-12)
100/9 x^-4
sqrt( 100/9 x^-4)
Put the negative exponent in the denominator and make it positive
sqrt( 100 / (9x^4) )
We know that sqrt( a / b) = sqrt(a) / sqrt( b)
sqrt(100)
----------------
sqrt( 9x^4)
10
-------------
3x^2
Read more on Brainly.com - brainly.com/question/12900964#readmore
Answer:
thirty
Step-by-step explanation:
The answer is A. Those are the four points that are graphed.
Answer: D
Step-by-step explanation:
Look at the exponents first and order them from least to greatest